New recommendations for management of eating disorders (anorexia nervosa, bulimia nervosa) from NICE - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
The UK’s National Institute for Health and Care Excellence (NICE), one of the most authoritative institutions in the field of evidence-based medicine, has issued standards for management of patients with anorexia and bulimia nervosa.